Improving Students' Learning Motivation in Islamic Religious Education: A Collaborative Learning Management Approach Based on Games and Flashcards - Sufirmansyah Sufirmansyah; Agus Dwi Santosa; Siti Rimayatul Fadhilah; Shahzadi Hina Sain (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2026)
This study aims to analyse the effectiveness of the Game-Based Learning (GBL) model combined with flashcard media in increasing student learning motivation in Islamic Religious Education subjects. This study is based on constructivist theory and learning motivation theory, which emphasises the importance of active involvement, enjoyable learning experiences, and providing challenges as drivers of students' intrinsic motivation. The study used a mixed methods approach with a convergent design, involving 33 grade 10 students as research subjects. Quantitative data were obtained through learning motivation observation sheets using a Likert scale, while qualitative data were collected through direct observation of student activities during the learning process. The results showed that the application of Game-Based Learning assisted by flashcard media was able to significantly increase student learning motivation, indicated by 82% of students who were in the high and very high motivation categories after the intervention. In addition, game-based learning was able to increase active participation, enthusiasm, group collaboration, and student courage in expressing opinions during the learning process. The novelty of this study lies in the integration of the Game-Based Learning model with flashcard media implemented in the context of Islamic Religious Education learning in Pesantren-based vocational schools. This combination produces a learning strategy that not only increases learning motivation but also creates a more interactive, collaborative, and enjoyable learning experience, so that it has the potential to become an innovative learning model that is relevant for application in Islamic educational institutions